Pengaruh Dosis Herbisida Campuran Metil Metsulfuron 0,7% + Chlorimuron Etil 0,7% + 2,4-D Na 75% terhadap Gulma, Pertumbuhan dan Hasil Padi (Oryza sativa L.) pada Sistem Tanpa Olah Tanah - Dedi Widayat; Uum Umiyati; Yayan Sumekar; Citra Berta W Gultom (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2018)
Zero tillage system and herbicides are widely used to overcome the lost of yield due to the weeds. Herbicides are used in this experiments were herbicides active inggredients mixture ofmethylmetsulfuron 0.7% + chlorimuron ethyl 0.7% + 2,4-DNa 75%. This experiment aims to determine the effect of mixed herbicide methyl metsulfuron 0.7% + chlorimuron ethyl 0.7% + 2.4-D Na 75% to the weeds, growth and yield of Ciherang varieties of rice crops on the Landless system. The experiment was held in October 2016 until January 2017 at SPLPP (Sanggar Penelitian Latihan dan Pengembangan Pertanian) Faculty of Agriculture UNPAD Raya Laswi Street Numb. 176 Jelekong Bale Endah Subdistrict, Bandung Regency, West Java. The experiments used a Randomized Block Design with 7 treatments and 4 replications, they are : A. Methylmetsulfuron 0.7% + chlorimuron ethyl 0.7% + 2,4-DNa 75% 750 g / ha, B. Methylmetsulfuron 0.7% + chlorimuron ethyl 0.7% + 2,4-DNa 75% 1000 g / ha, C. Methylmetsulfuron 0.7% + chlorimuron ethyl 0.7% + 2,4-DNa 75% 1250 gr / ha, D. Methylmetsulfuron 0.7% + chlorimuron ethyl 0.7% + 2,4-DNa 75% 1500 gr / ha, E. Manual weeding + OTS (maximum tillage), F.Maximum tillage (OTS) + without weeding. The result of the research showed that various doses of herbicide mixture of methyl metsulfuron 0,7% + chlorimuron ethyl 0,7% + 2,4-D Na 75% give effect to suppressionthe weight of weeds and not give effect to the growth and yield of rice crops. Key words : Weeds, methylmetsulfuron 0.7% + chlorimuron ethyl 0.7% + 2,4-DNa 75% , Rice Crop, Zero Tillage System